Parental Feeding Practices, Self-efficacy and Maternal Attitudes with Sonoran Preschool Children - Campos Rivera, Nora Hemi (Consorcio de Universidades Mexicanas A.C., 2021)
The objective of this study was to analyze the relationship between attitudes, maternal self-efficacy, and parental feeding practices as it relates to overweight and obese children. Three hundred mothers with at least one child between 3 and 7 years of age (Mage = 5.43, SD = 6.1) attending first to third grade at the elementary level, from among eleven kindergartens in a northwestern Mexican city were included in the study. The age of the Mothers ranged between 20 and 50 years (Mage = 30.99, SD = 6.1). For this study, we used The Attitudes, Beliefs and Feeding Practices Questionnaire, the Self-Efficacy Scale and the Scale of Maternal Attitudes towards Childhood Overweight and Obesity. We found that the perceived child´s weight is associated with the perceived mother´s weight; attitudes towards excess weight are linked to parental feeding practices.